2019
DOI: 10.18203/2320-6012.ijrms20190023
|View full text |Cite
|
Sign up to set email alerts
|

The morphologic relationship of the lesser trochanter with the femoral neck and greater trochanter

Abstract: Background: The anatomy of the proximal femur comprises important landmarks for many orthopedic surgical procedures. However, this area exhibits morphological differences depending on race, gender and age. Besides being the insertion area of the hip flexor muscles, the lesser trochanter is also used as an angular reference in many orthopedic surgical procedures. The aim of this study is to investigate the morphologic relationship of the lesser trochanter with the femoral neck and greater trochanter.Methods: Ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…The mean length of the intertrochanteric crest of the right femur was 5.92± 0.52 cm, and the left femur was 6.20±0.87 cm, and their difference was identified to be statistically significant. Akkaya et al [31] suggested that the length of the intertrochanteric crest of the right femur was 67.5±4.9 mm, and of the left femur was 67.5±4.9 mm, which is almost to our findings. Khanal et al [21] studied the measurements of proximal and distal fragments in the Nepalese population and found the length of the intertrochanteric crest of the right femur was 5.10 ±0.74 cm of the left femur was 4.98±0.66 cm which is lower than our study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The mean length of the intertrochanteric crest of the right femur was 5.92± 0.52 cm, and the left femur was 6.20±0.87 cm, and their difference was identified to be statistically significant. Akkaya et al [31] suggested that the length of the intertrochanteric crest of the right femur was 67.5±4.9 mm, and of the left femur was 67.5±4.9 mm, which is almost to our findings. Khanal et al [21] studied the measurements of proximal and distal fragments in the Nepalese population and found the length of the intertrochanteric crest of the right femur was 5.10 ±0.74 cm of the left femur was 4.98±0.66 cm which is lower than our study.…”
Section: Discussionsupporting
confidence: 90%
“…A measure of association between two variables is defined as the correlation [31]. The weight-bearing bones of the lower limb have the highest degree of correlation with stature [13] Chandran, in his study on South Indian females, concluded that all the incomplete measurements showed a positive correlation with the femoral length.…”
Section: Discussionmentioning
confidence: 99%